2016
DOI: 10.1155/2016/3068430
|View full text |Cite
|
Sign up to set email alerts
|

Chain Length and Thermal Sensitivity of the Infrared Spectra of a Homologous Series of Anhydrous Silver(I)n-Alkanoates

Abstract: The thermal and chain length sensitivity of the infrared spectra of some solid state anhydrous silver(I) salts (n-octanoate to n-eicosanoate, inclusive) are discussed. At ambient temperature, the tilted alkyl chains, anchored to the metal planes via chelating bidentate coordination to the silver ions, are crystallized in the fully extended all-trans conformation. Interestingly, though all compounds are crystallized in a monoclinic crystal system, their lateral chain packing, van der Waals effects, and hence vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Likewise, for amino acids, shifts of wavenumbers would be expected since they have non-polar short chains. Similarly, it has been reported that the displacements of the signals associated with CH bonds are related to molecular packaging [64] , [65] ; thus, a decrease in packing will be associated with greater freedom of movement and consequently greater vibrational energy (displacement of signals at higher wavenumbers) [65] . The above is important because a weakening of the yeast cell envelope of C. albicans , due to the presence of H. pylori , could manifest itself in a shift to larger wavenumbers; likewise, a restriction of freedom of movement would be associated with shifts to lower wavenumbers.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Likewise, for amino acids, shifts of wavenumbers would be expected since they have non-polar short chains. Similarly, it has been reported that the displacements of the signals associated with CH bonds are related to molecular packaging [64] , [65] ; thus, a decrease in packing will be associated with greater freedom of movement and consequently greater vibrational energy (displacement of signals at higher wavenumbers) [65] . The above is important because a weakening of the yeast cell envelope of C. albicans , due to the presence of H. pylori , could manifest itself in a shift to larger wavenumbers; likewise, a restriction of freedom of movement would be associated with shifts to lower wavenumbers.…”
Section: Resultsmentioning
confidence: 71%
“…In relation with the mechanism 1, it has been reported that the union of alkyl groups to polar groups, e.g., carbonyl, is affected in their vibratory movements as a function of the length of the alkyl chain [64] . In this way, for shorter chain length is greater the effect of polar groups, and conversely, as the chain length increases, the vibratory movements become independent of the influence of polar groups.…”
Section: Resultsmentioning
confidence: 99%
“…The transmission IR spectra of Ag(I) 2,2-dimethylbutanoate ( Figure 3 a) and Ag(I) benzoate ( Figure 3 b) obtained from the as-synthesised compounds agree well with previous results [ 21 , 37 , 38 , 39 ]. However, the positions of the asymmetric carboxylate stretching vibration ν as (COO − ) at 1544 and 1553 cm −1 are indicative of a dominant contribution of ligands with a monodentate coordination [ 40 , 41 , 42 , 43 ]. The transmission IR spectrum of Ag(I) benzoate exhibits an additional band at 1517 cm −1 , which is characteristic of a bridging coordination [ 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the positions of the asymmetric carboxylate stretching vibration ν as (COO − ) at 1544 and 1553 cm −1 are indicative of a dominant contribution of ligands with a monodentate coordination [ 40 , 41 , 42 , 43 ]. The transmission IR spectrum of Ag(I) benzoate exhibits an additional band at 1517 cm −1 , which is characteristic of a bridging coordination [ 40 , 41 , 42 , 43 ]. Only the bridging coordination is observed in the ATR–IR and RAIR spectra of both Ag(I) 2,2-dimethylbutanoate and Ag(I) benzoate.…”
Section: Resultsmentioning
confidence: 99%
“…There has already been discussion of these modes being largely from the alkyl chains of the WC14 rather than the EO segment, [4,31] allowing the analysis of the conformational order of the hydrophobic WC14 chains independent of EO. Highly ordered crystalline Ag-adsorbed alkanes have their ν s and ν as methylene vibrations at around 2847 and 2916 cm -1 [32]. A departure to the higher wavenumbers from those positions attests to the increase in structural flexibility and gauche defects.…”
Section: Spectroscopic Characterisations Of Anchoring Samsmentioning
confidence: 99%